Mini review of neonatal maladjustment syndrome in horses (Revista Sistemas de Producción Agroecológicos, 2024)
Neonatal maladjustment syndrome, also called neonatal encephalopathy, perinatal asphyxia, hypoxic-ischemic encephalopathy, and “dumb foal” syndrome, occurs in foals suffering from hypoxia, as well as those suspected of experiencing an altered transition from intrauterine to extrauterine life. However, the etiology is unknown since it may have multiple origins. The primary symptoms include seizures, blindness, vocalizations, wandering, tonic-clonic contractions and loss of the sucking reflex, as well as described in other cases a failure in thermoregulation, seizures and alterations of other body organ systems, such as decreased motility of the gastrointestinal tract. Regarding its pathophysiology, it derives from two moments, the first due to a process of acute cerebral ischemia and energy and oxygen deficit; the second is due to a process of the metabolic neurotransmitter or endocrine imbalances where the inhibitory effects of neurosteroids (adenosine, allopregnanolone, pregnenolone and prostaglandin D2) still present after birth and are believed to be partially responsible for the alteration of consciousness. Treatments usually focus on clinic neonate signs, so pregnancy control in mares and calving accompaniment are essential to prevent this syndrome.
Keywords: asphyxia; encephalopathy; neonates; foals